Nonlinear Associations between Blood Cadmium Concentration and Thyroid Hormones According to Smoking Status in Korean Adults: The Korea National Health and Nutrition Examination Survey (KNHANES) - Byungmi Kim; Minshik Rhie; Sunhee Park; Hyo-Seon Kim; Jeoung A Kwon (Toxics, 2023)
Research on the association between blood cadmium (BCd) exposure and thyroid hormone levels in the general population has been inconclusive. Therefore, we examined the associations between BCd and thyroid hormones according to smoking status in Korean adults (N = 1170, Men = 722, Women = 448) using multiple linear regression and restricted cubic splines analysis with data from the Korean National Health and Nutrition Examination Survey (2013). The geometric mean of BCd was 0.74 μg/L in all study participants and was higher in smokers (1.01 μg/L) than in nonsmokers (0.65 μg/L). Restricted cubic splines analysis revealed nonlinear trends between BCd and free thyroxine in smokers (p for nonlinearity = 0.02). By contrast, there were no significant associations between BCd and thyroid hormones in either men or women. In conclusion, nonlinear associations may exist between BCd and free thyroxine in smokers. Our study provides empirical support for the future formulation of an acceptable concentration range of BCd and offers a new concept for preventing thyroid problems.